2017
DOI: 10.1080/17512433.2017.1253472
|View full text |Cite
|
Sign up to set email alerts
|

Mood Therapeutics: Novel Pharmacological Approaches for Treating Depression

Abstract: Introduction Real-world effectiveness trials suggest that antidepressant efficacy is limited in many patients with mood disorders, underscoring the urgent need for novel therapeutics to treat these disorders. Areas Covered Here, we review the clinical evidence supporting the use of novel modulators for the treatment of mood disorders, including specific glutamate modulators such as: 1) high-trapping glutamatergic modulators; 2) subunit (NR2B)-specific N-methyl-D-aspartate (NMDA) receptor antagonists; 3) NMDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 122 publications
(123 reference statements)
0
15
0
Order By: Relevance
“…Additionally, these medications might take up to several weeks to induce pharmacological effects and patients often drop-off treatment because of a variety of unwanted secondary effects, which comprise insomnia, headache, sexual dysfunction, and dry mouth [38]. While novel therapeutic strategies are urgently needed for the management of MDD, PTSD, and other mood disorders, the nuclear receptors PPAR-α and γ are gaining consistent interest as new promising targets for treating behavioral dysfunction (please see Tables 1 and 2 for a summary) [39]. This is further substantiated by the recent discovery that stimulation of PPAR-α can enhance neurosteroid biosynthesis [10], which is implicated in the etiopathology of mood disorders and their treatment [7,[40][41][42][43].…”
Section: Mood Disordersmentioning
confidence: 99%
“…Additionally, these medications might take up to several weeks to induce pharmacological effects and patients often drop-off treatment because of a variety of unwanted secondary effects, which comprise insomnia, headache, sexual dysfunction, and dry mouth [38]. While novel therapeutic strategies are urgently needed for the management of MDD, PTSD, and other mood disorders, the nuclear receptors PPAR-α and γ are gaining consistent interest as new promising targets for treating behavioral dysfunction (please see Tables 1 and 2 for a summary) [39]. This is further substantiated by the recent discovery that stimulation of PPAR-α can enhance neurosteroid biosynthesis [10], which is implicated in the etiopathology of mood disorders and their treatment [7,[40][41][42][43].…”
Section: Mood Disordersmentioning
confidence: 99%
“…Depression is a mood disorder with complicated etiopathogenesis, with different subtypes (or variable endophenotypes) which differ across individual patients. This complexity is in addition to such major divisions among mood disorders as MDD, bipolar disorder and seasonal affective disorder 58 , Gecici and colleagues first investigated the relationship between leptin and different clinical subtypes of MMD and found that depressive patients with atypical symptoms had higher serum leptin levels than controls 59 . No differences were found between depressive patients with a more typical profile and controls 59 .…”
Section: Leptin and Depressionmentioning
confidence: 99%
“…On these bases, preventing hypercortisolemia has been recently considered as a novel pharmacological strategy for MDD and, in particular, for TRD (Henter et al, 2017). Mifepristone, a glucocorticoid receptor antagonist, seems to be efficacious in the treatment of TRD: Neurobiology and Identification of Novel Targets psychotic depression, a subtype of depression characterized by hypercortisolemia (Blasey et al, 2011), with a rapid improvement of depressive and psychotic symptoms (Belanoff et al, 2001(Belanoff et al, , 2002.…”
Section: Hypothalamic-pituitary-adrenal Axis Dysfunctionmentioning
confidence: 99%